TILEK HÁM ONÍŃ KELIP ShÍǴÍWÍ, ÓZINE TÁN ÓZGEShELIKLERI - Abdimuratov, Levitan Aymuratovich (SCIENCE and SOCIETY, 2026)
The article discusses the wish, which is a type of blessing used among our people in the traditional songs of the Karakalpak people, and its origins and specific features.